WATER MASSES CHARACTERISTICS AT THE SANGHIE TALAUD ENTRY PASSAGE OF INDONESIAN THROUGHFLOW USING INDEX SATAL DATA 2010 - Ivonne M Radjawane; Paundra P Hadipoetranto (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT Measurement of ocean physical parameters using the CTD was conducted by deep water expedition INDEX-SATAL 2010 (Indonesian Expedition Sangihe-Talaud) in July-August 2010. The aim of this study was to determine the characteristics of water masses around the Sangihe Talaud Water where there was an entry passage of Indonesian throughflow (ITF) at the west pathway that passed through the primary pathway i.e., the Sulawesi Sea and Makassar Strait and the secondary pathway (east pathway) that passed through the Halmahera Sea. The analyses were performed by the method of the core layer and was  processed with software Ocean Data View (ODV). The results showed that in the Sangihe Talaud waters there was a meeting water masses from the North Pacific and the South Pacific. The water mass characteristics in main pathway through the Sulawesi Sea was dominated by surface and intermediate North Pacific water masses and carried by the Mindanao Currents. While the Halmahera Sea water mass was dominated by surface and intermediate South Pacific water masses carried by the New Guinea Coastal Current that moved along the Papua New Guinea and Papua coast enters to the Halmahera Sea. Keywords: Index-Satal 2010, Northern Pacific Water Masses, Southern Pacific Water Masses, Sangihe Talaud